Ocular complications in children with Stevens-Johnson syndrome - Gotz-Więckowska, Anna; Bernardczyk-Meller, Jadwiga; Rakowicz, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Purpose: Presentation of serious cases of Stevens-Johnson syndrome (SJS) with acute and chronic ocular manifestations and methods of their treatment. Material and methods: 3 children aged between 6 to 12 years. Follow-up time was from 5 months up to 6 years. Conservative treatment was: symblepharon massage, topical antibiotics, steroids, artificial tears. In chronic stage mitomycin C as eye drops was use in one case. Surgical treatment - intubation of lacrimal ducts and removal of eye lashes were performed in 2 cases. Results: In 2 cases, in which ophthalmological therapy was introduced very early, the results of treatment were very good. In one case with corneal neovascularization and posterior lid margin keratinization, the results of treatment were not satisfactory. Conclusions: 1. The children with SJS should be treated by ophthalmologists as soon as possible. 2. Some pathological changes of conjunctiva, cornea and lacrimal ducts disapperared after few weeks of intensive topical therapy often. 3. The results of treatment of cicatrical changes of lids, conjunctiva and neovascularization of the cornea were not satisfactory.